IMPLEMENTATION OF SCIENCE LEARNING BASED ON ANIMATED VIDEOS IN ELEMENTARY SCHOOL - Rizka Safitri; Andi Prastowo (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
This study aims to find out how the implementation of science learning based on animated videos in elementary schools. This research uses a qualitative approach with a descriptive method. This research was conducted at Al-Fatih Integrated Islamic Elementary School. The subjects in this study were science lesson teachers in class V. The instrument used to collect data was in the form of semi-structured interview instruments. Data collection techniques with interviews. This data analysis technique is carried out by collecting data, then continued with the selection of the data obtained, after that continued with the presentation of data, and drawing conclusions. The implementation of learning in class is divided into three stages of implementation, namely initial activities, core activities, and closing activities. In the implementation of learning, teachers play an important role in transferring knowledge to students. Teachers need media that can help them in transferring knowledge. Animated videos are a medium that can help teachers transfer knowledge to students. The implementation of animated video-based science learning provides benefits and has a positive impact on students and teachers. Animated videos motivate students, increase students' interest and understanding and help teachers in providing concrete examples and creating a fun learning atmosphere